The Influence of Budget Preparation Participation on Managerial Performance with Organizational Commitment, Leadership Style and Motivation as Moderating Variables - Aliah Pratiwi; Reza Muhammad Rizqi (FEB Universitas Sultan Ageng Tirtayasa, 2023)
This research aims to test and analyze the effect of budget participation on managerial performance and to test and analyze the effect of budget participation on managerial performance with organizational commitment, leadership style and motivation as moderating variables. The population in this study were employees of PT. Port Indonesia III Bima Branch has 110 employees. The samples in the research were employees who held positions and were involved in budget preparation and had a minimum work period of one year during the budget preparation period. Based on these criteria, the total sample was 53 respondents. The data analysis tool uses Smart PLS 3.0. The research results show that budget participation has a positive and significant effect on managerial performance. The research results also show that organizational commitment has a positive and significant effect on the relationship between budget participation and managerial performance, then the research results state that leadership style has a negative and insignificant effect on the relationship between budget participation and managerial performance, and other results motivation has a negative and significant effect on the relationship between budget participation and managerial performance.